Analysis of Helicopter Landing Pad Planning in the Nagreg Area - Ruhiyat, Ade; Kusdian, R. Didin (Green Publisher Indonesia, 2026)
Road congestion along the Cileunyi–Nagreg corridor in West Java intensifies annually during the Eid homecoming period, yet the development of a heliport as an alternative solution remains underexplored. This study examines the urgency of heliport development in Nagreg and calculates the structural dimensions of its concrete slab system, including beam dimensions, slab thickness, and reinforcement requirements. Structural analysis was performed to determine internal forces and load redistribution under dead loads, live loads, and earthquake loads. Beam and slab elements were designed to ensure structural strength and stability, with reinforcement calculated based on the ratio of steel area to concrete area. The beam dimensions were determined as 200/400 mm in the x-direction and 203.75/407.5 mm in the y-direction. The concrete slab thickness was calculated to be 12 cm and reinforced with Ø12 mm bars at 120 mm spacing. Strength verification of the slab confirmed that the nominal moment capacity (Mn = 11.436 kNm) exceeds the required ultimate moment (Mu = 5.529 kNm), thereby confirming structural safety and compliance with applicable standards. The study concludes that heliport construction in Nagreg is technically feasible and structurally viable, offering a strategic alternative to mitigate recurring congestion. These findings provide a foundational technical framework for heliport development in similarly congested corridors. Further research is recommended to assess economic feasibility, environmental impact, and integration with regional transportation master plans.